PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN PAIR CHECK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELASIXF SMP NEGERI 1 SIAK HULU - Mahanawan, Arisnani Mahanawan Arisnani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research was based on the students achievement in learning mathematics especially grade IXFSMP Negeri 1 Siak who achieve the Criteria of Minimum Achievement percentage is 28,125%. The subject of basic competence were about similarity. The teacher-centered learning was still used to teach materials during the learning process. The research conducted was the Classroom Action Research. This research aims to improve learning process and mathematics learning outcomes in SMP Negeri 1 Siak Hulu by implementingcooperative learning model of Pair Check approach in mathematics lesson.This research is aclassroomaction research with twocycles. Each cyclehas fourstages, thestagesareplanning, action, observationandreflection. Subjects of the research were studentsgrade IXFwhohave theacademicability oftheheterogeneous. The instrument of this research are learning equipment and collected data instrument. The learning equipment are consist of sylabus, learning plan program and student paper work, the collected data instrument are consist of observation paper and student learning outcome test. The technique of collected data of this research are observation and test technique. The analysis data tehnique in this research are teacher and student’s activities analysis, mathematic learning outcome analysis and the the success of action.Student mathematic learning outcome analysis are cinsist of development value of individual and group, reached of Criteria of Minimum Achievement for each indicator and reached Criteria of Minimum Achievement.The results showed the activity of teachers and students have done well after doing the action. An increase in the number of students who achieved at UH Criteria of Minimum Achievement end of each cycle compared to the number of students who achieve Criteria of Minimum Achievement on base score. The result of study in the first cycle found that the percentage of students who achieve Criteria of Minimum Achievement is 56,25% and the second cycle is 71,875%. Results of this research indicate that the implementing of cooperative learning model of Pair Check approach canimprove learning process and the mathematics learning outcomes of students grade IXFSMP Negeri 1 Siak Huluin the first semester academic year2013/2014. Key words:Learning process, Mathematics learning outcome, Cooperative learning, Pair Check, Classroom action research.